Influence of printing direction on the dynamic response of additively-manufactured polymeric materials and lattices. (September 2022) - Sun, Z.P.; Guo, Y.B.; Shim, V.P.W.
Highlights: Influence of printing angle on rate-sensitivity of FDM-fabricated PLA material. Angle-dependent strut material causes anisotropy of lattices comprising octet and HS cells under impact. A constitutive model of strut material with both rate and angle dependence factored in. FE models incorporating the established constitutive model capture anisotropy of lattices observed. Relationship between the change of cell deformation mode and anisotropy of lattices. Abstract: Additive manufacturing techniques facilitate fabrication of polymeric lattice structures comprising complex cell architectures, via the ability to fabricate component struts at specified angles. However, the inherent layer-wise fabrication process, especially for Fused Deposition Modelling (FDM), introduces angle-dependent properties depending on the orientation with respect to the printing bed. This results in lattices displaying different mechanical responses, depending on the direction of loading. The present study examines how the static and dynamic tensile material properties of cell strut material are influenced by the angle of printing. Specimens printed at various angles were subjected to quasi-static tensile loading, as well as dynamic extension using a tensile split Hopkinson bar device. It was found that the degree of rate-sensitivity depends on the printing angle. Octet and Hybrid Structure (HS) lattices were also fabricated and subjected to quasi-static and impact compression along the printing direction and transverse to it. The results show that the load-deformation responses and lattice crushing patterns differ significantly. Finite element models, incorporating both printing angle and rate dependent strut material and failure properties, were established, to analyse the deformation with respect to loading direction, at both lattice sample and cell-component levels.